(untitled) (Academia Science Repository, 2023)
The article deals with the creation of an army consisting of Turks, Fergana, and warriors from Ustrshana, which is the basis of the military power of the Abbasid Caliphate of the Samarra period, its importance in the life of the caliphs of the Abbasid dynasty, the reasons for founding the city of Samarra, which served as the residence of the caliphs and the capital of the empire for almost half a century. The relationship of soldiers from the guards and their commanders with the caliphs, the impact on the political life of the caliphate.